Acute redistribution of regional left ventricular work by cardiac resynchronization therapy determines long-term remodelling. (7th February 2020) - Duchenne, Jürgen; Aalen, John M; Cvijic, Marta; Larsen, Camilla K; Galli, Elena; Bézy, Stéphanie; Beela, Ahmed S; Ünlü, Serkan; Pagourelias, Efstathios D; Winter, Stefan; Hopp, Einar; Kongsgård, Erik; et al.
Abstract: Aims : Investigating the acute impact of cardiac resynchronization therapy (CRT) on regional myocardial work distribution in the left ventricle (LV) and to which extent it is related to long-term reverse remodelling. Methods and results : One hundred and thirty heart failure patients, referred for CRT implantation, were recruited in our prospective multicentre study. Regional myocardial work was calculated from non-invasive segmental stress–strain loop area before and immediately after CRT. The magnitude of volumetric reverse remodelling was determined from the change in LV end-systolic volume, 11 ± 2 months after implantation. CRT caused acute redistribution of myocardial work across the LV, with an increase in septal work, and decrease in LV lateral wall work (all P < 0.05). Amongst all LV walls, the acute change in work in the septum and lateral wall of the four-chamber view correlated best and significantly with volumetric reverse remodelling ( r = 0.62, P < 0.0001), with largest change seen in patients with most volumetric reverse remodelling. In multivariate linear regression analysis, including conventional parameters, such as pre-implant QRS morphology and duration, LV ejection fraction, ischaemic origin of cardiomyopathy, and the redistribution of work across the septal and lateral walls, the latter appeared as the strongest determinant of volumetric reverse remodelling after CRT (model R 2 = 0.414, P < 0.0001). Conclusion : The acute redistribution of regional myocardial work between the septal and lateral wall of the LV is an important determinant of reverse remodelling after CRT implantation. Our data suggest that the treatment of the loading imbalance should, therefore, be the main aim of CRT.